2016
DOI: 10.12659/msm.897773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mir-21 on Cardiac Microvascular Endothelial Cells After Acute Myocardial Infarction in Rats: Role of Phosphatase and Tensin Homolog (PTEN)/Vascular Endothelial Growth Factor (VEGF) Signal Pathway

Abstract: BackgroundThis study investigated how miR-21 expression is reflected in acute myocardial infarction and explored the role of miR-21 and the PTEN/VEGF signaling pathway in cardiac microvascular endothelial cells.Material/MethodsWe used an in vivo LAD rat model to simulate acute myocardial infarction. MiR-21 mimics and miR-21 inhibitors were injected and transfected into model rats in order to alter miR-21 expression. Cardiac functions were evaluated using echocardiographic measurement, ELISA, and Masson stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…The osteogenic differentiation could be regulated by miR-145 through targeting FOXO1 [37]. Moreover, the effects of FOXO1 on cell biological function and inflammatory reaction have been previously reported [38,39]. Therefore, we considered that the regulatory effects of miR-145 on VECs proliferation and migration and inflammation in ACS might be achieved by targeting FOXO1.…”
Section: Discussionmentioning
confidence: 98%
“…The osteogenic differentiation could be regulated by miR-145 through targeting FOXO1 [37]. Moreover, the effects of FOXO1 on cell biological function and inflammatory reaction have been previously reported [38,39]. Therefore, we considered that the regulatory effects of miR-145 on VECs proliferation and migration and inflammation in ACS might be achieved by targeting FOXO1.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has indicated that cardiac angiogenesis had a close association with heart failure, while interestingly CMECs play a regulatory role in the process of cardiac angiogenesis (Ma et al, ). For example, miR‐21 shows protective effects against CMEC injury through the PTEN/VEGF signaling pathway following acute myocardial infarction (F. Yang et al, ). Additionally, miR‐200a rescues CMECs in the settings of hypoxia‐reoxygenation injury through mediating the protection of thymosin β4 (Y. Li, Zhu, Liu, Du, & Yu, ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to vascular injury, resveratrol attenuates endothelial function during hyperglycemia via activation of proteasome-dependent degradation of PTEN, which in turn increases Akt phosphorylation (36). Furthermore miR-21 exerts protective effects on endothelial injury through the PTEN/VEGF pathway after acute myocardial infarction (37). Thus, PTEN might be involved in the functional regulation of GECs.…”
Section: Discussionmentioning
confidence: 99%